Career intentions and satisfaction influences in early career Australian physiotherapists - Paynter, Sophie; Iles, Ross; Hodgson, Wayne C.; Hay, Margaret (Physiotherapy theory and practice, 2024)
The current workforce does not meet the demand for physiotherapy services in Australia. Future demand is predicted to expand driven primarily by the aging population. Previous research describes significant attrition and short career intentions of junior physiotherapists. This study explored factors associated with physiotherapy graduates' early career intentions and satisfaction. Four cohorts of student physiotherapists completed two online surveys designed specifically for this study assessing their immediate and future career intentions and satisfaction. Surveys were completed after undergraduate training (Student Survey) and 2 years later (Practitioner Survey). Question formats included single or multiple select, Likert scale, and free-text responses. Responses were analyzed via descriptive statistics and content and relational analysis. Despite most early career practitioners (83%) reporting career satisfaction, 27% intended to pursue long-term physiotherapy careers (>20 years) and 15% intended to work for 5 years or less. Fewer (11%) reported a longer career intention and 26% a shorter career intention compared to their student survey. Extrinsic occupational factors, such as support, were mentioned as influential in increasing intended future career length since course completion. This study found some evidence of factors contributing to shorter career intentions of early career physiotherapists. Specific support of early career physiotherapists may encourage longer career intentions and help build future workforce capacity.